2020
DOI: 10.1093/ehjcr/ytaa082
|View full text |Cite
|
Sign up to set email alerts
|

False-positive troponin elevation due to an immunoglobulin-G-cardiac troponin T complex: a case report

Abstract: Background Troponin is a crucial biomarker for the diagnosis of an acute coronary syndrome (ACS). It rises in response to myocardial injury from significant acute myocardial ischaemia caused by obstructive coronary artery disease [‘classical’ myocardial infarction (MI)]. However, raised levels have also been noted in conditions not recognized as classical ACS. This may include MI with non-obstructed coronary arteries such as takotsubo cardiomyopathy and other acute or chronic conditions such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In our case, it was not possible to confirm the presence of the analytical interference in cTnI concentrations before AMI, but it is equally true that it cannot be excluded that it occurred secondary to the cardiac ischemic injury. Although mainly anecdotal cases are reported in the literature [ 13 ], evidence has recently become available regarding the prevalence and clinical impact of troponin macroforms. Warner et al report the presence of a high-molecular-weight immunoglobulin-cTnI complex in 5% of patients with elevated cTnI concentrations [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, it was not possible to confirm the presence of the analytical interference in cTnI concentrations before AMI, but it is equally true that it cannot be excluded that it occurred secondary to the cardiac ischemic injury. Although mainly anecdotal cases are reported in the literature [ 13 ], evidence has recently become available regarding the prevalence and clinical impact of troponin macroforms. Warner et al report the presence of a high-molecular-weight immunoglobulin-cTnI complex in 5% of patients with elevated cTnI concentrations [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of macrotroponin (macroTn) indicating formation of immunoglobulin-troponin complexes, is also coming to attention in the ICI population, where immune activation may result in autoantibody binding to circulating cTn, forming a macrocomplex. Initially considered a spurious cTn result finding, macroTn has been reported with all cTn assays and has been associated with myocarditis and cardiomyopathy (40)(41)(42). While clinical implications of macroTn in ICI-myocarditis remain an area of active investigation, elevated cTn must always be interpreted in conjunction with clinical context.…”
Section: Clinical Caveats For Applying Ctns In Surveillance Diagnosis...mentioning
confidence: 99%
“…The overall prevalence of antitroponin antibodies and macrotroponin remains elusive, because they are usually assessed only in extreme cases of clinical and biological discordance and not routinely or systematically. 10 Previous studies have showed that the involvement of macrotroponin could range between 5% and ~50% in patients with an increased cTn result depending on the context and the assays. 8 , 54 MI with nonobstructive coronary arteries is a recently defined heterogeneous clinical entity characterized by nonobstructive coronary arteries on coronary artery angiogram (≤50% stenosis) and without an overt cause for the MI, such as cardiac trauma or injury.…”
Section: Unresolved Issuesmentioning
confidence: 99%
“… 7 Macrotroponin has become more of a challenge since the use of hs‐cTn (high‐sensitivity cTn) assays, 8 and several cases of misinterpreted troponin elevation related to antibodies and macrotroponin have been reported. 10 , 11 , 12 Thus, although cTn is a powerful and recognized marker of myocardial injury, cTn results are not undisputable and should always be interpreted within the clinical context, especially in case of mismatch between the clinical scenario and the result of the cTn assay (Figure 1 ).…”
mentioning
confidence: 99%